Analysis of Strategy and Teamwork on Sales Effectiveness at PT Sumber Jaya Motor Honda Medan - Rumapea, Elsa Oktavera; Siboro, Indah Putri; Yasir, Nabila Utami; Silitonga, Thresia Putri; Syahreza, Dina Sarah; Harmen, Hilma (Economic: Journal Economic and Business, 2025)
This study analyzes the influence of marketing strategies and teamwork on sales effectiveness at PT Sumber Jaya Motor Honda Medan. The marketing strategies implemented include promotions through events, brochure distribution, and the use of social media to reach consumers. Solid teamwork between departments, such as marketing, sales, and customer service, is the key to implementing these strategies effectively. The results of the study show that although the sales contribution from promotional events is relatively small, social media and brochure distribution have a significant impact on increasing sales. Synergy between teams allows companies to maximize the potential of marketing strategies, increase brand awareness, and maintain competitiveness in the automotive market.